Relationship between Mindfulness and Quality of Life in Early Adulthood during the COVID-19 Pandemic - Marchelina Febe (UM Purwokerto Press, 2021)
This study aims to see whether awareness impacts the quality of life in early adulthood, especially during the Covid 19 pandemic. This research was conducted because Indonesia is currently experiencing the Corona Virus, better known as Covid 19, which is known to be known. This pandemic has a carom effect on many aspects. The public has started to feel the impact of the Corona Virus more than recently. Many people feel bored, cannot be productive, and even feel sad because of this situation. So that began to be done various ways to overcome this effect so as not to spread more widely. One of them is mindfulness, which is expected to affect how a person thinks and later will impact the quality of one’s life. The quality of life itself is very influential in a person’s life because it is related/covers almost all aspects of life, starting from emotional, social, and even physical in one’s life. If the quality of life is good, it cannot make someone feel prosperous and impact happiness, creativity, productivity, etc. Therefore, researchers want to see whether one’s awareness can affect aspects of the quality of life with this pandemic. This quantitative research uses a questionnaire as the primary data technique and uses SPSS ver.26 for data processing. The results showed that mindfulness has a relationship or can affect a person’s quality of life, especially individuals in early adulthood.